The Use of Echocardiography and Advanced Cardiac Ultrasonography During Pregnancy - O’Kelly, Anna C. (Curr Treat Options Cardiovasc Med, 2019)
PURPOSE OF REVIEW: Pregnancy is a time of significant cardiovascular change. Echocardiography is the primary imaging modality used to assess cardiovascular anatomy and physiology during pregnancy. Both two-dimensional (2D) echocardiography and advanced cardiac ultrasound modalities play pivotal roles in identifying and monitoring these changes, especially in women with preexisting or new cardiac disease. This paper reviews the role of echocardiography and advanced cardiac ultrasound during normal pregnancy and pregnancy complicated by hypertensive disorders, valvular disorders, and cardiomyopathy. It also examines the role of echocardiography in guiding decisions about delivery. RECENT FINDINGS: The data establishing normal echo parameters during pregnancy are inconsistent. In addition, there is limited research exploring the role of advanced cardiac ultrasound modalities, such as tissue Doppler imaging or speckle tracking echocardiography, in assessing cardiac function during pregnancy. What data there are suggest that these advanced modalities can be used to identify subclinical changes before traditional echocardiography can, and thus have clear utility in identifying early abnormal cardiac responses to pregnancy. SUMMARY: Echocardiography is the modality of choice for imaging the heart in pregnant women. Advanced ultrasound modalities increasingly play a role in identifying abnormal adaptations to pregnancy and detecting subclinical changes. This, in turn, can help promote a healthy pregnancy for both mother and fetus.